Service Design and Delivery - Macintyre, Mairi; Parry, Glenn; Angelis, Jannis (Service Science: Research and Innovations in the Sevice Economy, 1865-4924, 2011)
Service Design and Delivery provides a comprehensive overview of the increasingly important role played by the service industry. Focusing on the development of different processes employed by service organizations, the book emphasizes management of service in relation to products. It not only explores the complexity of this relationship, but also introduces strategies used in the design and management of service across various sectors, highlighting where tools, techniques and processes applicable to one sector may prove useful in another. The implementation methods introduced in the book also illustrate how and why companies can transform themselves into service organizations. While the book is primarily intended as a text for advanced-level courses in service design and delivery, it also contains theoretical and practical knowledge beneficial to both practitioners in the service sector and those in manufacturing contemplating moving towards service delivery.